The Influence of Empowerment on the Entrepreneurial Ability of Micro Enterprises in Surabaya City - Ardela Putri Amalia; Sri Wibawani; Erwing Wahyu Millensyah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The ability of micro enterprises to grow and adapt is important in advancing the national economy. Therefore, supporting the empowerment of micro enterprises by the government is a strategic step that needs to be taken. The Surabaya City Government supports the empowerment of micro enterprises by stipulating Surabaya City Regional Regulation No. 1 of 2021. The Culinary Tourism Center (SWK) is an empowerment facility spread across 51 locations in Surabaya City and has accommodated 1,217 micro enterprises. However, in its development, micro enterprises face the problem of SWK conditions that are empty of visitors and limited understanding of digital marketing. Therefore, the purpose of this study was to examine the influence of micro enterprise empowerment on the ability of micro enterprises in the Culinary Tourism Centers of Surabaya City. This study uses an associative quantitative method to measure the extent to which micro enterprise empowerment (X) affects micro enterprise abilities (Y). The sample included 100 micro enterprises from 51 SWK, chosen through simple random sampling. The data analysis technique used regression analysis with SPSS version 30. The research findings show that variable X significantly and positively affects variable Y, evidenced by a significance level below 0.001 (p < 0.05) and a t-value of 10.332, which exceeds the critical t-value of 1.66055. Additionally, the coefficient of determination (R²) is 0.521, showing a strong relationship between the two variables. Despite the positive results, the Surabaya City Government still needs to design and implement a strategic empowerment concept with clear Standard Operating Procedures.